Postconcussive Symptoms and Neurocognitive Function after Mild TBI - J Gordon Millichap (Pediatric Neurology Briefs)
The frequency, nature, and recovery from postconcussive symptoms (PCSs) after mild traumatic brain injury (MTBIs) are described in 28 patients, 10 to 17 years of age, and their neurocognitive function in the initial 4 to 5 weeks are compared with 45 injured controls without MTBIs, in a prospective, longitudinal study at University of Michigan, Ann Arbor, MI.